Tauhid Dan Hukum Tentang Bangsa-Bangsa (Telaah atas Pemikiran Ismail Raji Al-Faruqi) - Sangkot Sirait (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
For al-Faruqi, Islam is an-all encompassing ideology, the primeryidentity of aworld-wide community of believers and the guiding principle forsociety and culture. This approach, this wholistic Islamic world-view, is embodiedin a life and career in which he wrote extensively, lectured and consulted withIslamic movements and national governements and organized Muslims in bothAmerica, for instance, and internationally. Al-Faruqi, who saw the world throughthe prism of his Islamic faith and commitment, focused on issues of identity,history, belief, culture, social mores and international relations. Al-Faruqi, waspreoccupied with the specific scheme of Urubahor Arabism. He described Arabism as an Arab stream where the Arabness, in fact, animates that stream andgives it momentum and provides them with their language, culture and religion.From this, he light the conceft of ummah as basis of the concept of state inwhich there are peole who has rights and duties. His pax Islamica which stoodon his arm was never conceived as monolithic society in which Islam alone predominates. To enter into the paxIslamica never meant coversion to Islam,but entry into a peacepul relationship where ideas are free to move and men arefree to convince and be convinced. Indeed, the Islamic state put all its resourcesat the disposal of all believers.